Total Factor Productivity Growth and the Environment: A Case for Green Growth Accounting - Anastasios Xepapadeas; E. Tzouvelekas; D. Vouvaki (Fondazione Eni Enrico Mattei (FEEM), 2007)
We examine whether the use of the environment, proxied by CO2 emissions, as a factor of production contributes, in addition to conventional factors of production to output growth, and thus it should be accounted for in total factor productivity growth (TFPG) measurement and deducted from the .residual. A theoretical framework of growth accounting methodology with environment as a factor of production which is unpaid in the absence of environmental policy is developed. Using data from a panel of 23 OECD countries, we show that emissions. growth have a statistically significant contribution to the growth of output, that emission augmenting technical change is present along with labor augmenting technical change, and that part of output growth which is traditionally attributed to technical change should be attributed to the use of the environment as a not fully compensated factor of production. Our results point towards the need for developing a concept of Green Growth Accounting.
Keywords: O47; Q2; 330; Solow Residual; Total Factor Productivity Growth; Growth; Environment; Green Growth Accounting; Produktivität; Umweltbelastung; Wachstumstheorie; Welt